2013
DOI: 10.18584/iipj.2013.4.1.2
|View full text |Cite
|
Sign up to set email alerts
|

The Physical and Mental Health of Off-Reserve First Nations Children of Teen Mothers

Abstract: The teen birth rate for First Nations women is higher than the teen birth rate for non-Aboriginal women. While associations between physical and behavioural outcomes have been examined in non-Aboriginal children with teen mothers, fewer studies have focused on First Nations children of teen mothers. This study uses data from the 2006 Aboriginal Children's Survey to compare physical and mental health outcomes of 2-to 5-year-old off-reserve First Nations children of teenage and older mothers. There were few diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
1
6
1
Order By: Relevance
“…Previous studies suggested that associations between child developmental delay and maternal age could be explained by socio-economic status, parenting behavior and home environment [22,34,35], and maternal depression [7]. In our study, those maternal associated factors were not significantly different between adolescent and adult mothers.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Previous studies suggested that associations between child developmental delay and maternal age could be explained by socio-economic status, parenting behavior and home environment [22,34,35], and maternal depression [7]. In our study, those maternal associated factors were not significantly different between adolescent and adult mothers.…”
Section: Discussioncontrasting
confidence: 54%
“…The Lancet series reviewing the maternal and child malnutrition in low-income and middle-income countries showed that the prevalence of stunting and wasting of children under five years was relatively higher in south Asia and subSaharan Africa [19]. Pregnant adolescents have a higher risk of malnutrition [19] which can result in growth failure [20,21] and developmental delay [14] and may subsequently reflect abnormal psychological behaviors in adolescence [4,22].…”
Section: Introductionmentioning
confidence: 99%
“…Among Inuit as well as other populations, low income and low education have been extensively studied and are common socio-economic factors associated with teenage pregnancy (13,14). Living in an overcrowded house and in a house in need of major repairs are the factors that have been linked to teenage pregnancy among Inuit and First Nations from Canada (15).…”
Section: Possible Determinantsmentioning
confidence: 99%
“…Unfortunately, few studies have addressed children's health problem taking into account the issue of the early age of Inuit mothers. Guèvremont (13), in her analysis of the population-based 2006 Aboriginal Children's Survey from Canada including Métis, Inuit and First Nations, found that 2- to 5-year-old Inuit children born from mothers having delivered their baby before the age of 20 compared to ≥25 years presented no differences in the incidence of chronic health conditions. While children from younger mothers were less likely to be found in excellent/very good health in this same study, this association disappeared after accounting for socio-economic factors.…”
Section: Impactmentioning
confidence: 99%
See 1 more Smart Citation